Breast Cancer and Molecular Medicine - Piccart, Martine J.; Hung, Mien-Chie.; Solin, Lawrence J.; Cardoso, Fatima; Wood, William C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
Molecular-based medicine is taking center stage due to the increasing knowledge of breast cancer molecular biology. Treatment tailoring is no longer a dream for the future, but the main goal of current research. This book provides an overview of the most recent techniques, agents and approaches for breast cancer that contribute to the individualization of treatment. Current biomedical research focuses on facilitating the transfer of molecular biology knowledge into the clinical management of patients, leading to increased survival as well as improved quality of life. Particular attention is given in this book to organ-specific tailored approaches, specific populations, patients$1 (Bpreferences and rehabilitation. Also discussed in depth are the respective roles of pharmacotherapeutics modelling, functional imaging, molecular staging, genomics and proteomics and their impact on the "re-classification" of breast cancer, as well as the clinical applications of basic science. The crucial issue of how to optimally integrate biological markers, new technologies and new diagnostic and therapeutic approaches into clinical trials and clinical practice is addressed. Combining the contributions from authors who are well known experts in these fields with editorial comments, this book provides an overview of the latest achievements in breast cancer and their use in clinical practice.s
Section 1 -- Role of Modeling in Pharmacotherapeutics -- Section 2 -- PET and Nuclear Medicine Imaging of the Breast -- Functional Radiologic Imaging in Breast Cancer -- Section 3 -- Prevention of Breast Cancer -- Section 4 -- DCIS: Pathology and Molecular Markers -- Ductal Carcinoma In Situ: a Modern Approach to Patient Management -- Ductal Carcinoma In Situ: Systemic Treatment -- Section 5 -- Tailored Surgery for Early Breast Cancer: Surgical Techniques -- Tailored Surgery for Early Breast Cancer: Biological Aspects -- Tailored Surgery for Early Breast Cancer: the Very Young Woman -- Tailored Surgery for Older Women with Breast Cancer -- Section 6 -- Tailored Radiotherapy for Breast Cancer Stages I and II: Technical Aspects -- Breast Cancer Management in the Era of Molecular Medicine: Tailored Radiotherapy $1 (BClinical and Biological Aspects -- Early Breast Cancer (Stage I and II): Tailored Radiotherapy for Very Young Women -- The Elderly and Breast Cancer Radiotherapy -- Section 7 -- Early Breast Cancer (Stage I and Stage II): Tailored Systemic Therapy for Endocrine-Resistant Breast Cancer -- Early Breast Cancer (Stage I and Stage II): Tailored Systemic Therapy for Endocrine-Responsive Breast Cancer -- Tailored Therapy for Breast Cancer in Very Young Women -- Tailored Systemic Therapy for the Elderly Woman -- Section 8 -- Locoregional Therapy Following Neoadjuvant Chemotherapy: an Evolving Paradigm of Treatment Individualization -- Medical Therapy of Locally Advanced Breast Cancer -- Section 9 -- Metastatic Breast Cancer: Tailored Endocrine Therapy for Premenopausal Women -- Metastatic Breast Cancer: Tailored Endocrine Therapy for Postmenopausal Women -- Metastatic Breast Cancer: Tailored Chemotherapy for the Elderly Woman -- Section 10 -- Treatment of Brain Metastases from Breast Cancer -- Surgical Management of Breast Cancer Liver Metastases -- Individualization of Bisphosphonate Therapy -- Breast Cancer Metastases to the Eye -- Organ-Specific Approaches: Pain Management -- Section 11 -- Genomic and Molecular Classification of Breast Cancer -- Applications of Proteomics to Clinical Questions in Breast Cancer -- Section 12 -- Targeting the HER Family of Receptors in the Treatment of Advanced Breast Cancer -- Biological Therapies for Metastatic Breast Cancer: Antiangiogenesis -- Breast Cancer Gene Therapy -- Innovative Rational-Derived, Target-Based and Cytotoxic Therapies for Breast Cancer and Other Malignancies -- Section 13 -- Mechanisms of Breast Cancer Resistance to Chemotherapy -- Mechanisms of Resistance to Hormone Therapy -- Novel Signaling Pathways in Breast Cancer -- Mechanisms of Apoptosis Resistance In Breast Cancer -- Section 14 -- Breast Cancer and Pregnancy -- Hormone Replacement Therapy After Breast Cancer -- Male Breast Cancer -- Patients$1 (BPreferences: What Makes Treatments Worthwhile? -- Breast Cancer: the Impact of Depression and its Treatment -- Molecular Profiling in Breast Cancer -- Clinical Trials in the Era of Treatment Tailoring.s
Keywords: Medicine; Gynecology; Radiotherapy; Oncology; Surgery; Medicine & Public Health; Oncology; Gynecology; Radiotherapy; Surgery; Electronic books